Origin of thick coal seam in the Gondwana sequence of Jamalgonj basin, Bangladesh (Journal of Nepal Geological Society, 1998)
The Jamalgonj basin is an E-W elongated graben/half-graben type intracratonic basin in the Stable Shelf/Bogra Slope of the Platform area of Bangladesh. The present basin area is more sagged and deepest part of the Permian basin and is thought to be the easternmost continuation of Gondwana basins in India. The basin contains Gondwana sequence (>555 m) with more than seven coal seams of variable thickness.The coals are high volatile bituminous type and contain high ash, low sulphur, moderate to high vitrinite, moderate inertinite, low exinite and high mineral matter. Lower seams are high in vitrinite than those of the upper. The coal seams contain several intraseam partings of shaley coal, coaly shale and carbonaceous shale/mudstone.The thick coal seams were deposited in moderately to poorly drained, densely vegetated and comparatively long persistent backswamps adjacent to the channel-floodplain environments of fluvial regime. This type of thick seams are thought to be formed due to the combined interaction of several factors such as, localised aggradation of fluvial channel, abandonment of part of the channel area, slow and steady subsidence, long and protected time of peat accumulation, favourable palaeoclimate, palaeoflora, etc. with variable magnitude.